Lateral Cervical Cyst: A Case Report (Indian Journal Of Clinical Practice, 2025)
Cystic degeneration of cervical lymph nodes is the most accepted theory for occurrence of lateral cervical cyst. It is commonlyfound in the anterior triangle of the neck, anterior to the upper third of the sternocleidomastoid. Clinical examination, imagingmodalities, such as ultrasonography, computed tomography (CT) and magnetic resonance imaging (MRI), and fine needleaspiration cytology (FNAC), are useful investigations to establish the diagnosis. Surgical excision of these lesions is reasonedcurative in most of the cases. Authors report a case of lateral cervical cyst which was successfully operated.